The Thematic Group of the Lexemes Denoting Foodstuff, Beverages and Kitchen Utensils in the Western Polissian Folklore Texts (Linguostylistic Studies, 2019)
The richness of the Ukrainian dialectal lexicon provide multifaceted opportunities for the study of its composition structure, the system of organization, features of functioning and its areal handling. The article, drawing on the materials of the folklore texts, provides a detailed analysis of the nomination processes, composition, structural organization, and semantics of the lexemes denoting foodstuff, beverages, and kitchen utensils in the Western Polissian dialect.The study has revealed that nominations of food are motivated mostly by the main ingredient of a dish, its taste, color, the holiday name for which the dish or product is intended, its shape, or purpose features, etc. Most of the detected lexemes are also commonly used in other Ukrainian language dialects. The nominations are described according to the lexical-semantic principle. In this article, 3 thematic subgroups (names of foodstuffs, names of beverages and names of kitchen utensils) are analyzed. A great variety of methods and techniques have been utilized to study the dialect vocabulary. The basic among them are the descriptive and analytical method (to systematize linguistic material and interpret the collected linguistic facts) and comparative-historical method (to find out the genesis of the lexical units). The study has revealed that modern rapid changes in nutrition give rise to the archaization of the traditional words in the lexical groups under consideration.The key findings of the research argue that the folklore texts reflect a limited proportion of the modern dialect vocabulary and. All the diversity of the folk vocabulary in the oral poetic texts cannot be represented in detail in the article due to the specific features of the selected material. The analyzed lexical content of the thematic groups of food, beverages, utensils contributes to the representation of the studied segment of the West Polissian dialect vocabulary in the Ukrainian continuum.
Keywords: dialectical vocabulary; Western Polissia; folklore texts; nomen; lexical-semantic group; names of foodstuffs and beverages; names of kitchen utensils